2019
DOI: 10.1136/bmjopen-2018-027807
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the success of vaginal birth after caesarean delivery: a retrospective cohort study in China

Abstract: ObjectivesTo develop a nomogram to predict the likelihood of vaginal birth after caesarean section (VBAC) among women after a previous caesarean section (CS).DesignA retrospective cohort study.SettingTwo secondary hospitals in Guangdong Province, China.ParticipantsInclusion criteria were as follows: pregnant women with singleton fetus, age ≥18 years, had a history of previous CS and scheduled for trial of labour after caesarean delivery (TOLAC). Patients with any of the following were excluded from the study: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 22 publications
12
35
1
6
Order By: Relevance
“…Almost all studies reveal the previous vaginal birth was found to be a strong predictor [2,3,9]. In our study, 96.4% of women with history of vaginal delivery had successful TOLAC.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Almost all studies reveal the previous vaginal birth was found to be a strong predictor [2,3,9]. In our study, 96.4% of women with history of vaginal delivery had successful TOLAC.…”
Section: Discussionsupporting
confidence: 50%
“…A trial of labor after Cesarean (TOLAC) can be a safe alternative and success rates are reported 60-80% [3,[7][8][9][10][11]. Successful TOLAC has many long-and shortterm benefits, including reduced perinatal complications, bleeding, thrombosis, and infection, and later life, chronic pain and ileus [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The larger sample size later in 2014–2015, however, provided a more reliable result. Recent domestic reports showed similar VBAC rate, ranging from 76.7%–87.2% (Li et al, ; Xing et al, ; Yang et al, ). In contrast to the rates reported in a literature review between 60%–77% (Tanos & Toney, ), the relatively higher outcome might be caused by the times of previous C‐S.…”
Section: Discussionmentioning
confidence: 74%
“…The larger sample size later in 2014-2015, however, provided a more reliable result. Recent domestic reports showed similar VBAC rate, ranging from 76.7%-87.2% (Li et al, 2019;Xing et al, 2019;. In contrast to the rates reported in a literature review between 60%-77% (Tanos & Toney, 2019) Our midwifery clinic aims at a caseload model to provide antepartum care for first, second and third trimester so that assessment and guidance can fit in the characteristics of each period.…”
Section: Discussionmentioning
confidence: 96%
“…The literature also indicated that other strategies are feasible. Li et al's retrospective cohort study demonstrated that trial of labour after caesarean delivery may be a potential strategy for decreasing the CSD rate [80]. This steady decline of CSD, particularly significant among nulliparous and multiparous births without a uterine scar, which is concomitant with a decline in perinatal mortality from 10.1 per 1,000 births to 7.2 per 1,000 births, is the result of institutional interventions and policy change [81].…”
Section: Intercontinental Comparison Of Csd Outcomesmentioning
confidence: 99%